Significance of lipid peroxidation processes in renal excretory dysfunction in cases of acute blood loss complicated by limb ischemia-reperfusion and its correction - Shatskyi, V. V.; Hudyma, A. A. (Journal of Education, Health and Sport, 2019)
Introduction. Activation of lipid peroxidation processes, which are exacerbated in cases of limb ischemia-reperfusion associated with temporary application of a tourniquetis a key mechanism of acute blood loss. However, its significance in the pathogenesis of renal dysfunction is understudied. The information on the effectiveness of carbacetam administration under these conditions, which has an antioxidant effect, is lacking. Objective. The aim of the research was to investigate the significance of lipid peroxidation processes in renal excretory dysfunction in cases of acute blood loss complicated by limb ischemia-reperfusion, and to evaluate the effectiveness of carbacetam for correction of these disorders. Materials and methods. The experiments were performed on 108 nonlinear male rats weighing 160-180 g. All animals were divided into five groups: a control group and four experimental groups (6 rats in each).The first experimental group comprised the animals anesthetized with thiopental sodium, in which a two-hour limb ischemia was simulated with further reperfusion. In the second experimental group the acute blood loss in the amount of 20-22% of a circulating blood volume was simulated to the anesthetized animals by femoral vein dissection. In the third experimental group these injuries were combined. In the fourth experimental group the animals with acute blood loss complicated by limb ischemia-reperfusion were administered with carbacetam intraperitoneally at a dose of 5 mg per kilogram of animal weight for correction. In the control group, the animals were anesthetized with equivalent dose of thiopental sodium; a tourniquet was applied for 2 hours without stopping the blood flow, and subsequently studied in 1 hour. In 1 and 2 hours, as well as in 1, 7and 14 days, the renal function was assessed in the experimental animals by means of the water loading test. Urine was collected for 2 hours and diures is was determined. After urine collection, the rats were anesthetized with thiopental sodium andtakenout of the experiment by total bloodletting from the heart. Concentrations of sodium in the urine and serum, as well as protein in the urine were determined. According to these data, sodium and protein excretion wasassessed. Additionally, the content of reagents with regard to thiobarbituric acid –TBA-active products of lipid peroxidation, was determined in the renal medulla. Results and discussion. In cases of limb ischemia-reperfusion, acute blood loss and their combination, the content of TBA-active products of lipid peroxidation in the renal medulla increased the most in 1 day. Up to the 14thday, the index decreased, but did not reach the level of the control group and was significantly higher in the group of animals with acute blood loss complicated by limb ischemia-reperfusion. In cases of the simulated injuries, increased sodium and protein excretion was evidenced compareto the control group. The highest increase in these parameters corresponded to the maximum activation of lipid peroxidation in the renal medulla in relation to the terms, and according to the amplitude increased from the group with limb ischemia-reperfusion to the group with acute blood loss and then to the group with combination of these disorders. This pattern was manifested the most significantly in 7-14 days of the reperfusion period. In case of carbacetam administration, the content of TBA-active products of lipid peroxidation and sodium excretionin the renal medulla significantly decreased in 7-14 days, compare to the animals without correction. Protein excretion decreased in 14 days of carbacetam administration. Taking into account the pronounced antioxidant properties of carbacetam, the attained result proved the significance of activation of lipid peroxidation processes in cases of kidney damage after limb ischemia-reperfusion, acute blood loss and their combination. Conclusions. With underlying limb ischemia-reperfusion, acute blood loss, and their combination, the sodium and protein excretion increase compare to the control group. The highest increase of these parameterstakes placein 1 day of the reperfusion period thatcorresponds to the maximal accumulation of TBA-active products of lipid peroxidation in the renal medulla in relation to the terms. The amplitude of changes in the studied parameters increases from the group of animals with limb ischemia-reperfusion to that with acute blood loss, and then to the group with their combination that is the most pronounced in 7-14 days of the reperfusion period. The carbacetam administration (at a dose of 5 mg per kilogram of animal body weight) causes a significant nephroprotective effect and up to the 14th day leads to a significant decrease in the content of TBA-active products of lipid peroxidation, reduced sodium and protein excretion in the renal medulla.